2010
DOI: 10.1097/ta.0b013e3181caa58f
|View full text |Cite
|
Sign up to set email alerts
|

Injury Severity and Quality of Life: Whose Perspective Is Important?

Abstract: ISS does not give the full picture of the severity of injury. Surgeons should consider early screening of patients for perception of injury severity and PTSD symptoms to determine which patients may need psychologic intervention to improve long-term QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 14 publications
11
51
0
4
Order By: Relevance
“…This reflects the mobility and diversity of the (poly)trauma patient population. High drop-out rates are not uncommon in the trauma literature, as previous studies with follow up rates of only 10% have been accepted [11]. Also, the mortality rate was high in our study.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This reflects the mobility and diversity of the (poly)trauma patient population. High drop-out rates are not uncommon in the trauma literature, as previous studies with follow up rates of only 10% have been accepted [11]. Also, the mortality rate was high in our study.…”
Section: Discussionsupporting
confidence: 47%
“…Recent publications in the Journal of Trauma have highlighted the importance of PTSD in the outcome of physical trauma [11,12]. These articles show that the outcome of complex orthopedic trauma patients is not only determined by obvious impairment, such as an amputation, but that pain and posttraumatic stress symptoms are very significant factors in determining outcome and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…A recent finding regarding the severity of the trauma as perceived by the patient and QOL six months posttrauma found that the severity of the trauma as perceived by the patient influenced the post-trauma QOL more than the trauma severity estimated by anatomical indicators, such as the Injury Severity Score. The results of that study suggest that the expectations of the patient regarding the injury play a more important role in the post-trauma recovery than the actual severity (10) .…”
Section: Discussionmentioning
confidence: 78%
“…This instrument has been demonstrated to have correlation with and sensitivity to the health problems present in HT victims, suggesting that it is adequate for the subjective evaluation of QOL in this population (9,10,(13)(14)(15) . Moreover, the SF-36 possesses a question that is not part of the evaluated items and, in an isolated form, allows the recognition of the interviewee's perception, negative or positive, regarding their health (11,12) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation